2018
DOI: 10.5937/straman1804032p
|View full text |Cite
|
Sign up to set email alerts
|

Participation of digital promotion in the promotional mix of small enterprises

Abstract: The digital revolution places the imperative of accepting the fact that all spheres of business must be modernized. As the core of all functions in the company changes, the marketing function changes. The marketing mix of companies is changing in terms of using digital technologies to implement marketing strategies. In addition to innovation in the domain of creating products, price construction and distribution channels, promotion is also being innovated. Communication of product offers to customers requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Research showed that in selling electronic home appliances, promotion through personal selling activities was the most effective (Qian et al, 2019). In small and medium-sized companies, research showed that company owners were satisfied with the designed promotional programs, both conventionally and digitally, to be able to reach more consumers and market share (Poljić et al, 2018).…”
Section: Promotionmentioning
confidence: 99%
“…Research showed that in selling electronic home appliances, promotion through personal selling activities was the most effective (Qian et al, 2019). In small and medium-sized companies, research showed that company owners were satisfied with the designed promotional programs, both conventionally and digitally, to be able to reach more consumers and market share (Poljić et al, 2018).…”
Section: Promotionmentioning
confidence: 99%
“…E-commerce will be the key to the competitiveness of traders, ensuring access to new market segments. (Dinu, 2007;Poljic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%